Preparation method of single-walled carbon nanotube composite silicon negative electrode material
By growing a composite of single-wall carbon nanotubes and nanosilicon particles in a high-temperature plasma arc reactor, the volume expansion problem of silicon-based negative electrode material is solved, an efficient and stable conductive network is achieved, and the cycle stability of lithium-ion batteries is improved.
Patent Information
- Application Number
- CN202411183268.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The volume expansion of silicon-based anode material during lithium embedding is severe, resulting in poor circulation stability and affecting battery safety and stability. The application of prior art in single-wall carbon nanotubes in silicon-carbon anode materials has difficulties in preparation.
The steam of the metal organic catalyst and cocatalyst is mixed with carbon source gas and gas-phase silane in a high-temperature plasma arc reactor to grow a composite of single-wall carbon nanotubes and nanosilicon particles, and the single-wall carbon nanotubes are obtained by acid purifying and purification. Composite silicon negative electrode material.
The uniform distribution of silicon nanoparticles in the single-wall carbon nanotube framework is achieved, particle collapse caused by volume expansion is avoided, and an efficient and stable conductive network is formed, which improves the stability of charge and discharge cycles.
Smart Images

Figure CN119143136A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of silicon-carbon negative electrode materials, and specifically provides a method for preparing a single-walled carbon nanotube composite silicon negative electrode material. Background Art
[0002] Silicon-based negative electrode materials have become a hot topic in the current research of lithium-ion batteries due to their huge theoretical specific capacity and abundant reserves. The theoretical capacity of silicon is as high as 4200mAh / g, which is more than 10 times that of traditional graphite, making silicon a strong candidate for the next generation of lithium-ion battery negative electrode materials. However, silicon will produce a volume expansion of up to 300% during the lithium embedding process. After multiple cycles, it will seriously damage the battery's conductive network, resulting in very poor cycle stability. At the same time, it seriously affects the safety and stability of the battery, which is a key factor restricting the large-scale application of silicon-based negative electrode materials. The method of particle nano-sizing, carbon coating and embedding in porous carbon skeletons is the current mainstream idea to solve the shortage of silicon-based negative electrode materials.
[0003] Chinese invention patent CN201210169022.1 invented a method for preparing silicon-carbon composite negative electrode materials for lithium-ion batteries. Nano-grinded silicon dispersion is added to graphite dispersion, and silicon atoms are dispersed on graphite nuclei by anion and cation charge adsorption method. After heat treatment, silicon-carbon negative electrode materials are obtained.
[0004] Chinese invention patent CN201010191897.2 proposes a method for preparing silicon-carbon negative electrode materials for lithium-ion batteries, wherein phenol monomers and aldehyde monomers are placed in a solvent for hydrolysis to synthesize a high specific area porous precursor, and then nano-silicon powder is added, and the special cavitation oscillation effect of ultrasound is used to effectively disperse the nano-silicon powder evenly in the synthesized high specific area porous precursor, and finally a high specific surface area porous polymer resin-coated silicon precursor is synthesized, dried and calcined, and finally a silicon-carbon negative electrode material is obtained. Single-walled carbon nanotubes have strong self-aggregation characteristics due to their huge aspect ratio and surface area, forming a stable conductive network, which can effectively solve the shortcomings of silicon-based negative electrode materials.
[0005] Wei Fei's team reported on the direct use of single-walled carbon nanotube film to load silicon materials for lithium battery negative electrode research. (Ziying He, Zhexi Xiao, Hongjie Yue, Yaxin Jiang, Mingyu Zhao, Yukang Zhu, Chunhui Yu, Zhenxing Zhu, Feng Lu, Hairong Jiang, Chenxi Zhang, Fei Wei, Single-Walled Carbon Nanotube Film as an Efficient Conductive Network for Si-Based Anodes, Adv. Funct. Mater. 2023, 2300094) First, a single-walled carbon nanotube film was prepared by floating chemical vapor deposition, and then the silicon-carbon material was spread on it, and then pressed into the gaps of the single-walled carbon nanotube film to prepare a flexible silicon-carbon negative electrode material.
[0006] However, due to the harsh preparation technology of single-walled carbon nanotubes and the harsh conditions for the preparation of silicon-based materials, the current application of single-walled carbon nanotubes in silicon-carbon negative electrodes is in the form of dispersed slurry or film, and there are great challenges in preparing composite materials in one step. Summary of the invention
[0007] In view of the above problems, the present invention provides the following technical solutions: A method for preparing a single-walled carbon nanotube composite silicon negative electrode material, the method comprises the following steps: mixing the vapor of a metal organic catalyst and a promoter with a carbon source gas and gaseous silane, and introducing the mixture into a plasma arc reactor driven by a carrier gas, and cracking and growing the mixture into a single-walled carbon nanotube and nano-silicon particle composite under the action of high-temperature plasma, and then obtaining the single-walled carbon nanotube composite silicon negative electrode material through acid washing and purification.
[0008] Furthermore, the implementation process of the method includes the following steps: S1) mixing an organic metal catalyst and a co-catalyst in a certain proportion, and conveying them to a catalyst evaporator heated to 150-500° C. under the driving force of a carrier gas to generate mixed vapor A of the organic metal catalyst and the co-catalyst; S2) Start the plasma arc furnace, introduce arc gas and strike the arc to generate a plasma arc, and raise the furnace temperature to 800-1800°C; S3) Mixing the mixed steam A, the carbon source gas and the gaseous silane gas, and introducing them into a plasma arc furnace driven by a carrier gas, and collecting the primary product B of single-walled carbon nanotubes and silicon nanoparticles at the outlet; S4) The primary product B is purified by acid washing to finally obtain the single-walled carbon nanotube composite silicon negative electrode material.
[0009] Furthermore, the organic metal catalyst in S1) is ferrocene, nickelocene, cobaltocene, ferric acetylacetonate, nickel acetylacetonate, cobalt acetylacetonate, carbonyl iron or a mixture thereof.
[0010] Furthermore, the co-catalyst is sulfur powder, selenium powder, thiophene, carbon disulfide or a mixture thereof. Furthermore, the mass ratio of the organometallic catalyst to the co-catalyst is 50:1 to 2:1, and the feed rate is 0.1 to 50 g / min; The carrier gas is nitrogen, argon, helium, hydrogen, or any one, two or three or more mixed gases in any ratio, with a flow rate of 0.1-20 L / min.
[0011] Furthermore, the plasma arc furnace in S2) is a plasma arc furnace reactor of transferred arc, non-transferred arc or mixed arc, wherein: When the plasma arc furnace is a non-transferred arc plasma arc furnace reactor, the cathode is a refractory metal such as tungsten, the anode is graphite, and the reaction raw materials enter the plasma arc furnace reactor from the gap between the cathode and the anode; When the plasma arc furnace is a transferred arc plasma arc furnace reactor, the cathode is a hollow graphite electrode, the anode is iron, cobalt, nickel metal and alloys thereof, and the reaction raw materials enter the plasma arc furnace reactor from the hollow graphite cathode.
[0012] Furthermore, the plasma arc furnace has a power supply of 10-500 kW, a current of 100-5000 A, and a voltage of 10-250 V; The arc gas is any one of nitrogen, argon, helium, hydrogen, and water vapor, or a mixture of two or more of them in any ratio, with a flow rate of 10 L / min to 500 L / min.
[0013] Furthermore, the carbon source gas in S3) is any one of methane, ethylene, acetylene, propylene or propane; The carrier gas is a mixture of nitrogen, argon or helium and hydrogen; The volume fraction of the carbon source gas is 5~45%; the volume fraction of hydrogen is 0.1~80%, and the rest is carrier gas, with a volume fraction of 15~94.9% and a flow rate of 1 L / min~ 500 L / min.
[0014] Furthermore, the gas phase silane is any one of monosilane (SiH4) and disilane (Si2H6) or a mixture thereof, with a flow rate of 1~1000L / min.
[0015] Furthermore, the pickling and purification process in S4) is: The primary product B is placed in hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid or a mixture thereof, The concentration of the hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid or a mixture thereof is 0.1-20M, the temperature is 20-120°C, stirring is performed for 10 minutes-24 hours, filtering and washing until neutral, and then drying and collecting.
[0016] Compared with the prior art, the method for preparing a single-walled carbon nanotube composite silicon negative electrode material of the present invention has the following outstanding beneficial effects: (1) Using high-temperature plasma arc as the heat source, the silicon source quickly passes through the plasma arc flame, which has the characteristics of high efficiency, high speed and large temperature gradient, which is conducive to the formation of uniform nanoscale silicon particles; (2) The simultaneous growth of single-walled carbon nanotubes and the pyrolysis growth of silicon nanoparticles are beneficial to the uniform dispersion of silicon nanoparticles in the single-walled carbon nanotube skeleton, effectively restraining the volume expansion generated during subsequent charge and discharge applications, avoiding particle collapse, and forming an efficient and stable conductive network; (3) By simply adjusting the ratio of carbon source to silicon source, silicon-carbon negative electrode materials with different silicon-carbon ratios can be prepared to meet different application requirements, with the significant advantages of high efficiency and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic diagram of the process flow of the method of the present invention; Figure 2 This is an electron microscope scan of the single-walled carbon nanotube composite silicon negative electrode material prepared by the present invention; Figure 3 is the Raman spectrum; Figure 4 It is the electrochemical cycle charge and discharge life curve. DETAILED DESCRIPTION
[0018] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Example 1
[0019] A method for preparing a single-walled carbon nanotube composite silicon negative electrode material, the preparation process is as follows Figure 1 As shown, proceed as follows: Step 1) The organic metal catalyst ferrocene and the co-catalyst sulfur powder are mixed in a ratio of 20:1, and transported to a catalyst evaporator heated to 300°C under the drive of carrier gas argon to generate a mixed vapor A of the organic metal catalyst and the co-catalyst, wherein the feed rate is 2 g / min and the carrier gas flow rate is 1 L / min.
[0020] Step 2) start the plasma arc furnace, introduce argon arc gas and strike an arc to generate a plasma arc, and raise the furnace temperature to 1200°C, wherein the plasma arc furnace is a non-transferred arc plasma arc furnace with a power supply of 100 kW, a current of 500 A, and a voltage of 200 V.
[0021] Step 3) Mix the mixed steam A with the carbon source gas, the carrier gas and the monosilane gas and introduce them into a plasma arc furnace, wherein the carbon source gas and the carrier gas component ratio is 25% methane, 20% hydrogen and 55% argon, the flow rate is 60 L / min, and the monosilane flow rate is 30 L / min; after the reaction is carried out, the primary product B of single-walled carbon nanotubes and silicon nanoparticles can be continuously obtained at the discharge port of the plasma arc furnace.
[0022] Step 4) The primary product B is placed in 4 M hydrochloric acid, stirred and soaked at 60° C. for 12 hours, filtered and washed until neutral, and then dried and collected to obtain the final single-walled carbon nanotube composite silicon negative electrode material C.
[0023] The product samples were collected and the morphology was observed using a scanning electron microscope. Figure 2 As shown; the crystallinity is evaluated by the peak intensity ratio of the G peak and the D peak in the Raman spectrum, as shown Figure 3 As shown, the G / D ratio is ~52.4. Then it is assembled with lithium iron phosphate into a button lithium battery, and its electrochemical cycle charge and discharge life curve is tested. The results are as follows Figure 4 shown. Example 2
[0024] Step 1) The organic metal catalyst ferric acetylacetonate and the co-catalyst thiophene are mixed in a ratio of 50:1, and transported to a catalyst evaporator heated to 500°C under the drive of carrier gas argon to generate a mixed vapor A of the organic metal catalyst and the co-catalyst, wherein the feed rate is 50 g / min and the carrier gas flow rate is 20 L / min.
[0025] Step 2) start the plasma arc furnace, introduce argon arc gas and strike an arc to generate a plasma arc, and raise the furnace temperature to 1800°C, wherein the plasma arc furnace is a transferred arc plasma arc furnace with a power supply of 500 kW, a current of 5000 A, and a voltage of 100 V.
[0026] Step 3) Mix the mixed steam A with the carbon source gas, the carrier gas and the monosilane gas and introduce them into a plasma arc furnace, wherein the carbon source gas and the carrier gas component ratio is 45% ethylene, 0.1% hydrogen and 54.9% argon, the flow rate is 500 L / min, and the monosilane flow rate is 500 L / min; after the reaction, the primary product B of single-walled carbon nanotubes and silicon nanoparticles can be continuously obtained at the discharge port of the plasma arc furnace.
[0027] Step 4) The primary product B is placed in 12M hydrochloric acid, stirred and soaked at room temperature for 24 hours, filtered and washed until neutral, and then dried and collected to obtain the final single-walled carbon nanotube composite silicon negative electrode material C.
[0028] The product samples were collected and their morphology was observed using a scanning electron microscope. Their crystallinity was evaluated using the peak intensity ratio of the G peak and the D peak in the Raman spectrum. They were then assembled with lithium iron phosphate into button-type lithium batteries, and their electrochemical cycle charge and discharge life curves were tested. Example 3
[0029] Step 1) The organic metal catalyst nickelocene and the co-catalyst selenium powder are mixed in a ratio of 2:1, and transported to a catalyst evaporator heated to 150°C under the drive of carrier gas argon to generate a mixed vapor A of the organic metal catalyst and the co-catalyst, wherein the feed rate is 0.1 g / min and the carrier gas flow rate is 0.1 L / min.
[0030] Step 2) start the plasma arc furnace, introduce argon arc gas and strike an arc to generate a plasma arc, and raise the furnace temperature to 800 °C, wherein the plasma arc furnace is a non-transferred arc plasma arc furnace with a power supply of 10 kW, a current of 100 A, and a voltage of 100 V.
[0031] Step 3) Mix the mixed steam A with the carbon source gas, the carrier gas and the disilane gas, wherein the carbon source gas and the carrier gas have a composition ratio of acetylene 5%, hydrogen 80% and argon 15%, a flow rate of 1 L / min, and a disilane flow rate of 1 L / min; after the reaction, the primary product B of single-walled carbon nanotubes and silicon nanoparticles can be continuously obtained at the discharge port of the plasma arc furnace.
[0032] Step 4) The primary product B is placed in 0.1 M nitric acid, stirred and soaked at 120° C. for 24 hours, filtered and washed until neutral, and then dried and collected to obtain the final single-walled carbon nanotube composite silicon negative electrode material C.
[0033] The product samples were collected and their morphology was observed using a scanning electron microscope. Their crystallinity was evaluated using the peak intensity ratio of the G peak and the D peak in the Raman spectrum. They were then assembled with lithium iron phosphate into button-type lithium batteries, and their electrochemical cycle charge and discharge life curves were tested. Example 4
[0034] Step 1) The organic metal catalyst cobaltocene and the co-catalyst carbon disulfide are mixed in a ratio of 10:1, and transported to a catalyst evaporator heated to 450°C under the drive of carrier gas argon to generate a mixed vapor A of the organic metal catalyst and the co-catalyst, wherein the feed rate is 10 g / min and the carrier gas flow rate is 5 L / min.
[0035] Step 2) start the plasma arc furnace, introduce nitrogen arc gas and strike an arc to generate a plasma arc, and raise the furnace temperature to 1100 °C, wherein the plasma arc furnace is a non-transferred arc plasma arc furnace with a power supply of 100 kW, a current of 500 A, and a voltage of 200 V.
[0036] Step 3) Mix the mixed steam A with the carbon source gas, the carrier gas and the monosilane gas and introduce them into a plasma arc furnace, wherein the carbon source gas and the carrier gas component ratio is 35% propylene, 10% hydrogen and 55% nitrogen, the flow rate is 100 L / min, and the monosilane flow rate is 30 L / min; after the reaction is carried out, the primary product B of single-walled carbon nanotubes and silicon nanoparticles can be continuously obtained at the discharge port of the plasma arc furnace.
[0037] Step 4) The primary product B is placed in 4 M hydrochloric acid, stirred and soaked at 60° C. for 12 hours, filtered and washed until neutral, and then dried and collected to obtain the final single-walled carbon nanotube composite silicon negative electrode material C.
[0038] The product samples were collected and their morphology was observed using a scanning electron microscope. Their crystallinity was evaluated using the peak intensity ratio of the G peak and the D peak in the Raman spectrum. They were then assembled with lithium iron phosphate into button-type lithium batteries, and their electrochemical cycle charge and discharge life curves were tested.
[0039] Comparative Example 1: In Comparative Example 1, the nano-dispersed slurry and the single-walled carbon nanotube dispersed slurry in the same proportion as in Example 1 were mixed, and the lithium battery silicon-carbon negative electrode was made through coating, drying, and rolling, and then assembled with lithium iron phosphate into a button-type lithium battery. The electrochemical cycle charge and discharge life curve was tested. The data of each embodiment and the comparative example are summarized in Table 1.
[0040] Table 1 <![CDATA[Raman spectrum average I G / I D > Specific capacity (mAh / g) Capacity retention rate after 500 cycles at 0.5C Example 1 75.4 2987.2 86.2 Example 2 54.5 2321.4 87.4 Example 3 70.2 2750.5 82.5 Example 4 65.7 2948.6 86.4 Comparative Example -- 1987.5 68.4 It can be seen from the above data summary that the embodiments of the present invention exhibit more superior charge and discharge cycle stability, and effectively overcome the deficiency of silicon-based negative electrode materials that electrode collapse occurs due to volume expansion and contraction during charge and discharge.
[0041] The embodiments described above are only preferred specific implementations of the present invention. Common changes and substitutions made by those skilled in the art within the scope of the technical solution of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a single-walled carbon nanotube composite silicon negative electrode material, characterized in that: The method comprises mixing the vapor of metal organic catalyst and promoter with carbon source gas and gas phase silane, cracking and growing into single-walled carbon nanotube and nano silicon particle composite under the action of high temperature plasma, and then obtaining the single-walled carbon nanotube composite silicon negative electrode material through acid washing and purification.
2. The method for preparing a single-walled carbon nanotube composite silicon negative electrode material according to claim 1, characterized in that: The implementation process of the method includes the following steps: S1) mixing the organic metal catalyst and the co-catalyst, and conveying them to a catalyst evaporator heated to 150-500° C. under the driving force of a carrier gas, to generate mixed vapor A of the organic metal catalyst and the co-catalyst; S2) Start the plasma arc furnace, introduce arc gas and strike an arc to generate a plasma arc, and raise the furnace temperature to 800~1800℃; S3) Mixing the mixed steam A, the carbon source gas and the gaseous silane gas, and introducing them into a plasma arc furnace driven by a carrier gas, and collecting the primary product B of single-walled carbon nanotubes and silicon nanoparticles at the outlet; S4) The primary product B is purified by acid washing to finally obtain the single-walled carbon nanotube composite silicon negative electrode material.
3. The method for preparing a single-walled carbon nanotube composite silicon negative electrode material according to claim 2, characterized in that: The organic metal catalyst in S1) is any one of ferrocene, nickelocene, cobaltocene, ferric acetylacetonate, nickel acetylacetonate, cobalt acetylacetonate, carbonyl iron, or a mixture of any two or more of them in any proportion.
4. The method for preparing a single-walled carbon nanotube composite silicon negative electrode material according to claim 2 or 3, characterized in that: The co-catalyst is any one of sulfur powder, selenium powder, thiophene and carbon disulfide, or a mixture of any two or more of them in any mixing ratio.
5. The method for preparing a single-walled carbon nanotube composite silicon negative electrode material according to claim 4, characterized in that: The mass ratio of the organometallic catalyst to the co-catalyst is 50:1~2:1, and the feed rate is 0.1~50g / min; The carrier gas is nitrogen, argon, helium, hydrogen, or any one, two or three or more mixed gases in any ratio, with a flow rate of 0.1-20 L / min.
6. The method for preparing a single-walled carbon nanotube composite silicon negative electrode material according to claim 3, characterized in that: The plasma arc furnace in S2) is a plasma arc furnace reactor of transferred arc, non-transferred arc or mixed arc, wherein: When the plasma arc furnace is a non-transferred arc plasma arc furnace reactor, the cathode is a refractory metal, the anode is graphite, and the reaction raw materials enter the plasma arc furnace reactor from the gap between the cathode and the anode; When the plasma arc furnace is a transferred arc plasma arc furnace reactor, the cathode is a hollow graphite electrode, the anode is iron, cobalt, nickel metal or its alloy, and the reaction raw materials enter the plasma arc furnace reactor from the hollow graphite cathode.
7. The method for preparing a single-walled carbon nanotube composite silicon negative electrode material according to claim 3, characterized in that: The plasma arc furnace has a power supply of 10-500 kW, a current of 100-5000 A, and a voltage of 10-250 V; The arc gas is any one of nitrogen, argon, helium, hydrogen, and water vapor, or a mixture of two or more of them in any ratio, with a flow rate of 10 L / min to 500 L / min.
8. The method for preparing a single-walled carbon nanotube composite silicon negative electrode material according to claim 3, characterized in that: The carbon source gas in S3) is any one of methane, ethylene, acetylene, propylene or propane; The volume fraction of the carbon source gas is 5~45%; the volume fraction of hydrogen is 0.1~80%, and the rest is carrier gas, with a volume fraction of 15~94.9% and a flow rate of 1 L / min~ 500 L / min.
9. The method for preparing a single-walled carbon nanotube composite silicon negative electrode material according to claim 3, characterized in that: The gas phase silane is any one of monosilane and disilane or a mixture thereof, with a flow rate of 1-1000 L / min.
10. The method for preparing a single-walled carbon nanotube composite silicon negative electrode material according to claim 3, characterized in that: The pickling and purification process in S4) is: placing the primary product B in hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid or a mixture thereof; The concentration of hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid or a mixture thereof is 0.1-20M, the temperature is 20-120°C, and the stirring is performed for 10 minutes to 24 hours; Filter and wash until neutral, then dry and collect.
Citation Information
Patent Citations
Material based on carbon and silicon nanotubes that can be used in negative electrodes for lithium batteries
CN101346834A
Preparation method of silicon carbide doped silicon powder and lithium battery silicon-carbon composite negative electrode material
CN117069115A
Preparation method and device for producing silicon-carbon negative electrode material of lithium battery by utilizing two-stage reactor method
CN117735530A
Carbon nanotube coated Si / SiOx composite negative electrode material and preparation method thereof
CN117810430A
Plasma fluidized bed and method for preparing single-walled carbon nanotubes
CN118477577A
Cited By
In-situ growth single-walled carbon nanotube coated silicon-carbon composite material and preparation method and application thereof
CN120793931A
